Optimization analysis of influencing factors on wind power integration based on continuous ant colony support vector machine - Du Qiushi; Lu Yu; Cong Li (China International Conference on Electricity Distribution, 2016)
In order to improve the reliability of wind power integration, using the continuous ant colony support vector machine theory based on the analysis of peaking need, we put forward the method of optimization analysis of influencing factors on wind power integration. According to the influence of parameter selection to optimization effect, we discuss the continuous ant colony support vector machine model and case study Wind Power Integration of Jilin Province. The result proves support vector function based on MG-CACO Algorithm improves the accuracy of the model, and it is very practical and effective in Wind Power Integration.